Topographical characteristics, diversity and utilization of saltlicks by Malayan Tiger (Panthera tigris jacksoni linnaeus) and potential prey at the Royal Belum Rainforest, Malaysia - Lazarus, Bryan Andrew (2021)
Natural saltlick (sira) is a place where a diverse of animals consume geophagy or drink water for mineral supplementation. Saltlicks are believed to be a key factor towards the density and distribution of all native wildlife species in the tropical and temperate rainforests. It’s also serves as rally points for wildlife species, as they determine the distribution and density of prey species which in turn affects predator population. Therefore, the objective of this study is to distinguish the topographic characteristics of different saltlicks in the Royal Belum rainforest. To achieve this objective, the topography of the saltlick and the prey-predator interactions around the saltlick were determined to identify the home-range of predator such as Malayan tiger. Three potential home ranges and their saltlick were identified based on the animal trail and foot print surrounding the home range; Sungai Tiang home range (e.g. Sira Kuak and Sira Tanah), ii) Sungai Kejar home range (e.g. Sira Rambai and Sira Bukit), and iii) Sungai Papan home range (e.g Sira Papan). The camera traps were placed at potential animal trails surrounding the saltlick. All captured images from the cameras were identified and tabulated according to the species density. Topography of the saltlick such as size, types, distance from the river and vegetation of the saltlick were recorded, and the wildlife densities were tabulated based on the camera traps. Results showed that Sira Kuak is near the main river and surrounded by dense shrubbery which provides ample camouflage for solitary herbivores such as muntjacs. Sira Batu is surrounded by rocky architecture and sub-canopy trees, hosting larger mammals such as elephants and tapirs whereas Sira Tanah is surrounded by a wide plain area with a small stream making it a suitable environment for herd animals such as sambar deer. The variation of topography has been suggested to affect the vulnerability of certain prey to predation by the predators due to changes in vegetation cover and food resources. This could indicate that topography is a crucial factor for wildlife in frequenting saltlicks for important physiological and sociological interactions. Further objectives were to determine tiger and potential prey diversity at the natural saltlicks as well as to determine species diversity utilization of saltlicks. Results also showed that all home range had non-significant different on the large bodied prey availability such as sambar deer (Rusa unicolor), muntjacs (Muntiacus muntjac) and wild pig (Sus scrofa). However, within a large area of sampling with over the period of two years, only one different individual tiger at Sungai Tiang, Sungai Papan and Sungai Kejar home ranges were sighted, and they were identified using their stripes. This could indicate that low availability and fewer predictable sites for prey aggregation in tropical forests may limit highly selective foraging decisions by the predators. Indeed, an individual tiger located around areas at natural saltlicks are dispersed and isolated around the Royal Belum Rainforest, which negatively affect physiological conspecific interactions leading to the inevitable decline of this species. This could suggest that Malayan tiger as solitary animals and spread across a large area of tropical rainforests will greatly reduce chances of encounter and mating, thus contributing towards the potential extinction in the Malaysia rainforest. In conclusion, the density and distribution of the prey species at the natural saltlicks is important for physiological and social interaction which in turn influenced the home-range of Malayan tigers.